Toxicity of Nanoparticles - Antonietta Zoroddu, Maria; Medici, Serenella; Ledda, Alessia; Marina Nurchi, Valeria; I. Lachowicz, Joanna; Peana, Massimiliano (Current Medicinal Chemistry, 2014)
Nowadays more than thousands of different nanoparticles are known, though no well-defined guidelines to evaluate their potential toxicity and to control their exposure are fully provided. The way of entry of nanoparticles together with their specificities such as chemistry, chemical composition, size, shape or morphology, surface charge and area can influence their biological activities and effects. A specific property may give rise to either a safe particle or to a dangerous one. The small size allows nanoparticles to enter the body by crossing several barriers, to pass into the blood stream and lymphatic system from where they can reach organs and tissues and strictly interact with biological structures, thus damaging their normal functions in different ways. This review provides a summary of what is known on the toxicology related to the specificity of nanoparticles, both as technological tools or ambient pollutants. The aim is to highlight their potential hazard and to provide a balanced update on all the important questions and directions that should be focused in the near future.
Keywords: Nanoparticles